Effect of diabetes mellitus on outcome of critically ill COVID-19 patients: A comparative study - Akshay Hiriyur Manjunathaswamy,; Nagashree Viswanath,; Smitha Malenahalli Chandrashekarappa,; Ramashetty, Rajalakshmi; Kalvapudi, Devaki (Asian Journal of Medical Sciences, 2022)
Background: Elderly population, individuals with metabolic derangements such as diabetes mellitus and obesity, and immunocompromised patients are falling prey to the severity of illness caused by the SARS-CoV-2 viral infection. India, deemed as the “Diabetes Capital of the World,” has a large population vulnerable to COVID-19 infection and its complications. Aims and Objectives: This study was conducted to measure, compare, and describe the clinical and biochemical parameters of COVID-19 patients admitted to the intensive care unit, with and without diabetes mellitus, and their outcomes in terms of morbidity and mortality. Materials and Methods: A cross-sectional comparative study was conducted on 146 hospitalized patients with COVID-19 disease confirmed with reverse transcription polymerase chain reaction, 66 of them categorized as diabetic and 80 as non-diabetic. Details of socio-demographic variables, medical history, and comorbidities of the patients were collected using a pre-tested and validated questionnaire. Vital signs and hematological, biochemical, and respiratory parameters were recorded and analyzed among both the groups of COVID-19 patients. Results: There were statistically significant differences in the age, sequential organ failure assessment scores at admission, SpO2, HbA1c, blood urea, creatinine, serum potassium, random blood sugar, ALT, pCO2, PaO2, acute respiratory distress syndrome (PaO2/FiO2), and the length of hospital stay between the diabetic and non-diabetic patients. Conclusion: Hospitalized patients with COVID-19 disease with diabetes mellitus have higher levels of inflammatory markers and of other predictors of severity of illness, need for admission in critical care units, and risk of in-hospital deaths compared to non-diabetic patients.